Family studying potential of philosophy of education. The majority in Ukraine, the idea of statehood as social challenge - Svitlana Cherepanova (International Society of Philosophy and Cosmology, 2015)
Takingintoconsiderationcontinualauthorialfamilystudyingexperienceofnationalupbringing of students it is grounded that within the defending of independence and European choice Majority in Ukraine gains the outlook-valuable sense as strategic social-integrating national idea and its realizations anticipate system regulation of social-humanities policy on the social, family and state level. Reviews and comments on the mentioned above idea are included. For the first time in domestic social science Family Studying is considered from position of Philosophy of Education, ontological personification of the culture individual through universal entirety of family, spiritual dialogue of generations. Then objective tendencies of intercultural harmonization of multinational surrounding of our country are considered. The research appeals to a wide research and education community, educators and students, culture activists, statesmen, politicians, economy and business, army, religious structures, nongovernment organizations and Mass Media - to all those interested in their own ancestry, family traditions, spiritual elevation of Ukrainian society.